Respuestas
Respuesta dada por:
0
a)
![2 \div 3 \times ( - 1) \div 5 = 6 2 \div 3 \times ( - 1) \div 5 = 6](https://tex.z-dn.net/?f=2+%5Cdiv++3+%5Ctimes+%28+-+1%29++%5Cdiv+5+%3D+6)
![\frac{2}{3} \times \frac{1}{5} = 6 \frac{2}{3} \times \frac{1}{5} = 6](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B3%7D++%5Ctimes++%5Cfrac%7B1%7D%7B5%7D++%3D+6)
![\frac{2}{15 } = 6 \frac{2}{15 } = 6](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B15+%7D++%3D+6)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años